Incidence and Severity of Drug Interactions Before and After Switching Antiretroviral Therapy to Bictegravir/Emtricitabine/Tenofovir Alafenamide in Treatment-Experienced Patients. (18th December 2020) - Schafer, Jason J; Pandit, Neha S; Cha, Agnes; Huesgen, Emily; Badowski, Melissa; Sherman, Elizabeth M; Cocohoba, Jennifer; Shimada, Ayako; Keith, Scott W
Abstract: Background: Switching antiretroviral therapy (ART) in people with HIV (PWH) can influence their risk for drug–drug interactions (DDIs). The purpose of this study was to assess changes in the incidence and severity of DDIs among PWH who switched their ART to bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF). Methods: This was a multicenter retrospective cohort study of PWH on ART and at least 1 concomitant medication (CM) who switched to BIC/FTC/TAF between 3/2018 and 6/2019. Using the University of Liverpool's HIV Drug Interaction Database, 2 DDI analyses were performed for each patient. The first assessed patients' preswitch ART regimens with their CM list. The second assessed the same CM list with BIC/FTC/TAF. Each ART-CM combination was given a score of 0 (no or potential weak interaction), 1 (potential interaction), or 2 (contraindicated interaction). A paired t test analyzed changes in total DDI scores following ART switches, and linear regression examined factors contributing to DDI score reductions. Results: Among 411 patients, 236 (57%) had at least 1 DDI present at baseline. On average, baseline DDI scores (SD) were 1.4 (1.8) and decreased by 1 point (95% CI, –1.1 to –0.8) after patients switched to BIC/FTC/TAF ( P < .0001). After adjusting for demographics, baseline ART, and CM categories, switching to BIC/FTC/TAF led to significant DDI score reductions in patients receiving CMs for cardiovascular disease, neurologic/psychiatric disorders, chronic pain, inflammation, gastrointestinal/urologic conditions, and conditions requiring hormonal therapy. Conclusions: Treatment-experienced PWH eligible to switch their ART may experience significant declines in number and severity of DDIs if switched to BIC/FTC/TAF.